WORKING IN INDUSTRIAL ENTERPRISES WAYS TO INCREASE THE EFFICIENCY OF ORGANIZING PROCESSES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Industrial enterprises have a special place in the sustainable development of the national economy. The article examines the improvement of the efficiency of the organization of production processes in industrial enterprises and provides recommendations.